Using QR-Code Flashcards with the Phonics Method to Improve Children's Phonics Skills - Dina Amalia; Aliva Rosdiana; Nur Alina Lailil Faroh; Rama Tri Nuryahya (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study addresses the low early reading proficiency of children aged 5–6 years and the limited use of interactive technology-based learning media in early childhood education. The study aimed to examine the effectiveness of QR-Code Flashcards integrated with the phonics method in improving children's early reading skills. A quantitative quasi-experimental design with a pretest–posttest control group was employed at TK Al Ikhlash Pekalongan, Jepara, involving 60 children (30 experimental; 30 control). Data were collected through early reading tests and classroom observation sheets and analyzed using descriptive statistics and an independent samples t-test. The results showed that the experimental group's mean score increased from 62.4 in the pretest to 85.7 in the posttest, with a gain of 23.3 points, while the control group improved from 61.8 to 72.3, with a gain of 10.5 points. Improvements were consistently higher in letter recognition (88.5), phoneme articulation (84.7), and vocabulary comprehension (83.9). The independent samples t-test indicated a statistically significant difference between the two groups (t (58) = 36.15, p < .001), demonstrating that QR-Code Flashcards integrated with the phonics method were significantly more effective than conventional flashcards. The findings indicate that integrating QR-Code technology with phonics instruction provides an effective multisensory learning approach that strengthens children's early reading skills and offers a practical innovation for early childhood literacy instruction in the digital era.